Small-Scale Wood-Fuelled CHP Plants: a Comparative Evaluation of the Available Technologies - S. Frigo; R. Gabbrielli; M. Puccini; M. Seggiani; S. Vitolo (Chemical Engineering Transactions, 2014)
Actually, several applications of small (=1 MWe) CHP (Combined Heat and Power) plants fuelled with solid wood can be found in Europe. Innovative technologies are facing the market, giving new perspectives for wood utilisation in district heating and/or in industrial-commercial activities. However, while the energy saving and the environmental benefits of CHP plants are undoubted, technological and no technological barriers still obstacle their large diffusion. The present study reports a comparative evaluation of the different available technologies in terms of thermal and electric efficiencies and their possible applications. Taking into consideration the electric-thermal performances of each configuration and the actual economic incentives guaranteed by the Italian government, a preliminary estimation of economic convenience of each plant is given.